The DNA damage checkpoint protein RAD9A is essential for male meiosis in the mouse - Vasileva, Ana (The Company of Biologists, 2013)
In mitotic cells, RAD9A functions in repairing DNA double-strand breaks (DSBs) by homologous recombination and facilitates the process by cell cycle checkpoint control in response to DNA damage. DSBs occur naturally in the germline during meiosis but whether RAD9A participates in repairing such breaks is not known. In this study, we determined that RAD9A is indeed expressed in the male germ line with a peak of expression in late pachytene and diplotene stages, and the protein was found associated with the XY body. As complete loss of RAD9A is embryonic lethal, we constructed and characterized a mouse strain with Stra8-Cre driven germ cell-specific ablation of Rad9a beginning in undifferentiated spermatogonia in order to assess its role in spermatogenesis. Adult mutant male mice were infertile or sub-fertile due to massive loss of spermatogenic cells. The onset of this loss occurs during meiotic prophase, and there was an increase in the numbers of apoptotic spermatocytes as determined by TUNEL. Spermatocytes lacking RAD9A usually arrested in meiotic prophase, specifically in pachytene. The incidence of unrepaired DNA breaks increased, as detected by accumulation of γH2AX and DMC1 foci on the axes of autosomal chromosomes in pachytene spermatocytes. The DNA topoisomerase IIβ-binding protein 1 (TOPBP1) was still localized to the sex body, albeit with lower intensity, suggesting that RAD9A may be dispensable for sex body formation. We therefore show for the first time that RAD9A is essential for male fertility and for repair of DNA DSBs during meiotic prophase I.